2002
DOI: 10.1590/s0100-879x2002000900008
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial antioxidant and oxidative stress changes due to sex hormones

Abstract: The purpose of the present study was to examine myocardial antioxidant and oxidative stress changes in male and female rats in the presence of physiological sex hormone concentrations and after castration. Twenty-four 9-week-old Wistar rats were divided into four groups of 6 animals each: 1) sham-operated females, 2) castrated females, 3) sham-operated males, and 4) castrated males. When testosterone and estrogen levels were measured by radioimmunoassay, significant differences were observed between the castra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
122
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 31 publications
16
122
3
4
Order By: Relevance
“…Also, cardiac tissue antioxidant enzymes were significantly lower in Ovx group than in control female group, and in Ovx+I/R group than in all other female groups. These results are in line with Barp et al (2002) and Kim et al (1998). On the other hand, Barp et al (2002) found that myocardial CAT activity was not significantly different between control male and female groups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Also, cardiac tissue antioxidant enzymes were significantly lower in Ovx group than in control female group, and in Ovx+I/R group than in all other female groups. These results are in line with Barp et al (2002) and Kim et al (1998). On the other hand, Barp et al (2002) found that myocardial CAT activity was not significantly different between control male and female groups.…”
Section: Discussionsupporting
confidence: 87%
“…These results are in line with Barp et al (2002) and Kim et al (1998). On the other hand, Barp et al (2002) found that myocardial CAT activity was not significantly different between control male and female groups. However, no other study investigated the differences in cardiac injury markers after renal I/R injury between males and females.…”
Section: Discussionsupporting
confidence: 87%
“…These observations provide evidence that testosterone deficiency contributes to the deterioration of antioxidant defense mechanisms in cardiomyocytes. In this respect, the results of our study are consistent with those reported by Barp et al (24) and Kłapcińska et al (25) in hearts and Meydan et al (23) in the hippocampal tissue. Data regarding the potential antioxidant role of exogenous testosterone in the heart are very scarce, and conflicting results have been observed in different tissues.…”
Section: Discussionsupporting
confidence: 93%
“…E. CRF + E 2 male group: reconstitution of central vein (**), mild congestion in chain reactions [13,14] and protect against atherosclerosis by binding free radicals. [40] Being a fat-soluble hormone, estrogen can contribute to membrane fluidity by direct interactions with phospholipids and attenuate the peroxidation of vascular smooth muscle cells and peroxidationinduced cell growth and migration. [41] On the other hand, age-related decline in estrogen secretion is accompanied by excessive oxidative stress and peroxidative cell damage, [42] which are known features of CRF.…”
Section: Discussionmentioning
confidence: 99%